(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation: Steam sterilizers are of great importance in the medical and pharmaceutical industries, and their main task is to clean equipment and materials from microorganisms. This work examines in detail the structure, maintenance measures and troubleshooting methods of steam sterilizers. Structurally, steam sterilizers use steam under pressure to carry out a disinfection process at high temperatures. Their main components are a boiler, a steam extraction system, control and automation devices, as well as sensors for measuring temperature and pressure. Maintenance measures are necessary to ensure the effective operation of sterilizers. These measures include regular cleaning, technical supervision and necessary repairs. Malfunctions can occur for various reasons, such as pressure drops, temperature changes or problems with the mechanical parts of the device. To eliminate these malfunctions, methods such as diagnostics, repairs and replacement of spare parts are used. This study provides important information for improving the efficiency of steam sterilizers and solving problems that arise during their use.